Estudo do comportamento em desgaste microabrasivo da liga Nb-Ni-WC-Cu sinterizada a plasma pulsado - Souza, Juliana Prates (2024)
There is an increasing demand in the industry for alloys with increasingly enhanced mechanical properties. Aiming at high-temperature applications, the Nb-Ni-WC-Cu alloy was developed in a previous study by spark plasma sintering (SPS) in three different nickel compositions (5%, 10%, and 15%) and sintered at three distinct temperatures (1000°C, 1100°C, and 1200°C). The objective of this work was to investigate the micro-abrasive wear behavior of this alloy. For this, Vickers hardness tests and micro-abrasion tests were carried out using three abrasives: alumina (Al₂O₃), silicon carbide (SiC), and silica (SiO₂). The results indicated that increasing the sintering temperature led to an increase in the hardness of the samples. The composition with 10% nickel sintered at 1100°C (M2 1100) showed the highest hardness (1345.80 HV). The micro-abrasion test was conducted in a fixed-ball configuration, with a load of 0.3 N and a rotation speed of 20 rpm, using an abrasive suspension with a concentration of 0.1 g/cm³ for Al₂O₃ and SiC, and 0.35 g/cm³ for SiO₂. The best results regarding abrasive wear were obtained for the samples sintered at 1100°C, for all compositions. Through scanning electron microscopy (SEM), it was observed that the predominant wear mechanism was grooving for the Al₂O₃ and SiO₂ abrasives, and rolling and mixed mechanisms for the SiC abrasive